Pelatihan Pembuatan Media Pembelajaran Berbentuk Video Animasi 3d Menggunakan Aplikasi Lumen untuk Meningkatkan Literasi Informasi pada Guru - Nyimas Muazzomi; Indryani Indryani; Mujahidawati Mujahidawati; Masyunita Siregar; Asih Nur Ismiatun; Febbry Romundza (Universitas Sebelas Maret, 2025)
Enhancing information literacy among teachers is a crucial step in supporting the achievement of quality education. Information literacy, which encompasses the ability to access, evaluate, and use information effectively, is vital in the learning process. With the advancement of technology, 3D animated video-based learning media has become a tool that can increase students' interest and understanding of the material being taught. This training aims to equip teachers with the skills to create learning media in the form of 3D animated videos using the Lumen application. This application is chosen for its ease of use in creating engaging and interactive visual content. In this training, participants will learn the basics of using Lumen, starting from 3D animation concepts, storyboard creation, to rendering and video editing techniques. The expected outcome of this training is the enhancement of teachers' competence in creating innovative and interactive learning media, which in turn can improve students' information literacy and understanding. Thus, this training is expected to contribute to improving the quality of education in schools.